Risk Perception of Coastal Communities and Authorities on Harmful Algal Blooms in Ecuador - Borbor-Córdova, Mercy J.; Pozo-Cajas, Mireya; Cedeno-Montesdeoca, Alexandra; Mantilla Saltos, Gabriel; Kislik, Chippie; Espinoza-Celi, Maria E.; Lira, Rene; Ruiz-Barzola, Omar; Torres, Gladys (Frontiers in Marine Science, 2018)
The ocean is intrinsically linked to human health as it provides food and wellbeing, yet shifts in its dynamics can pose climate-ecological risks, such as harmful algal blooms (HABs) that can impact the health and economy of coastal communities. For decades, Ecuadorian coastal communities have witnessed seasonal algal blooms, events that are driven by factors including complex ocean-climate interactions, nutrient availability, and ecological variables. However, little is known about the risk perceived by coastal populations regarding such events. Understanding how specific groups of people in specific places perceive HABs risks is critical for communicating, promoting, and regulating public health measures. This study assessed the knowledge, attitudes, and practices of fishermen, restaurant owners, and coastal authorities in relation to harmful algal blooms, or ‘red tide’ events, in coastal Ecuador. Methods utilized in this study include a non-probabilistic sampling approach for the two studied populations: coastal communities comprised of fishermen and restaurant owners (N1=181), and authorities comprised of coastal officials in the sectors of health, and environment and risk management (N2=20). Using contingency tables, chi-square test, Cramer’s V correlation statistic, and multiple correspondence analysis, this study compared the responses of these two groups, coastal communities, and authorities, to determine whether the principal activity or livelihood, affected risk perception in each group. This project implemented four workshops to interact with coastal stakeholders and more deeply understand risk perception within studied populations. Results demonstrated that principal activity indeed influenced risk perception of red tides and that fishermen, restaurant owners, and health authorities had limited knowledge and low-risk perception of red tide impacts on human health. Recommendations produced from this research include tailored workshops and improved communication between authorities and coastal communities to enhance algal bloom monitoring and coastal management during future red tide events.